Cardiovascular malformations in Turner's and Noonan's syndrome. - Van der Hauwaert, L G (1978)
The cardiovascular findings in 9 patients with Turner's syndrome and 9 patients with Noonan's syndrome are described. Of the 9 patients with Turner's syndrome, 4 had coarctation of the aorta, 4 aorta stenosis, and the remaining patient both these lesions. All patients with Noonan's syndrome had pulmonary valve stenosis. In addition, 2 children had an atrial septal defect and 1 an atrial septal defect associated with mild supravalvar pulmonary stenosis and anomalous drainage of the right upper pulmonary veins. In the majority of patients the electrocardiogram was different from the pattern usually seen in pulmonary valve stenosis: the QRS axis in the frontal plane was superiorly oriented in 7 out of 9 cases and in 2 patients evidence of right ventricular hypertrophy was lacking in the right praecordial leads; in 5 patients an rS complex was seen in the left praecordial leads. Gross thickening of pulmonary valve cusps was found at operation in 4 of the 8 patients who were operated on. Although phenotypically related, Turner's and Noonan's syndromes are associated with different and distinct cardiovascular anomalies.